Optics and Photonics for Advanced Dimensional Metrology 2020
DOI: 10.1117/12.2555035
|View full text |Cite
|
Sign up to set email alerts
|

Cascaded machine learning model for reconstruction of surface topography from light scattering

Abstract: In this paper, we propose a light scattering method to identify classes of structured surface topographies and estimate their main geometric properties. The method is based on a cascaded machine learning model, designed as a two-layer architecture implemented using neural networks. The first layer consists of a classification model designed to determine which type/class of surface is being observed amongst a set of predefined surfaces The second layer, cascaded to the first one, is designed to infer geometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…is very significant. The information is extracted and used by the neural network in the model training, making the model more accurate and effective [16]. Therefore, in this paper, the simulated texture was matched with the actual texture first, and then the simulated images and the actual images were input into the Xception model to predict the roughness.…”
Section: The Classification Results Of Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…is very significant. The information is extracted and used by the neural network in the model training, making the model more accurate and effective [16]. Therefore, in this paper, the simulated texture was matched with the actual texture first, and then the simulated images and the actual images were input into the Xception model to predict the roughness.…”
Section: The Classification Results Of Experimentsmentioning
confidence: 99%
“…To overcome the difficulty of obtaining samples of various roughness levels and compensate for the absence of training sample data, simulation can be used to generate a large number of surface images with roughness labels. Liu et al [16] proposed a light scattering method to identify classes of structured surface topographies and estimate their main geometric properties.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously developed a method to detect defects on surfaces featuring regular topographic patterns (e.g. gratings), based on using a light source to illuminate the surface, collect the scattered reflection pattern by using a sensor array, and finally analyse the pattern using machine learning to perform pattern classification and thus detect anomalies [23][24][25]. We have shown that using machine learning can solve the complex inverse scattering problem efficiently (compared to the traditional library search method [26]) and our solution based on combining light scattering and machine learning is relatively fast (compared to fringe projection methods [15,16]), thus suitable for application to in-process monitoring, and introduces minimal concerns in terms of process disturbance or accessibility issues.…”
Section: Introductionmentioning
confidence: 99%